All that glitters is not gold: The rise of gaming in the COVID-19 pandemic - M. Ángeles López-Cabarcos; Domingo Ribeiro Soriano; Juan Ramón Pi\~neiro Chousa (Journal of Innovation & Knowledge (JIK), 2020)
The COVID-19 pandemic has led to an unprecedented situation, with incalculable health, social, and economic consequences. At the start of the outbreak, the financial markets collapsed, although not all sectors suffered equally. The gaming and eSports industry is one of those that has suffered the least from the fall in the markets. Millions of people locked up at home, bored, stressed, and anguished, gave gaming and eSports companies growing prominence throughout the first half of 2020. This prominence has elicited interest in analyzing which variables can influence the returns in an industry in better financial health than many others. Using a logit-probit model, this research aims to analyze the relationship between financial (VIX, S&P GSCI Gold Index) and social (worldwide daily variation in total deaths from COVID-19 and worldwide Google attention on coronavirus) variables and the returns offered by the video game and eSports exchange traded fund (ESPO). The results show that the influence of social variables is weaker than the influence of financial variables. There is a significant inverse relationship between market volatility and ESPO returns and a highly significant relationship between ESPO returns and gold returns. While the relationship of ESPO returns with worldwide Google attention on coronavirus is significant, the relationship with worldwide daily variation in total deaths from COVID-19 is not. The conclusions of the study are discussed at the end of the paper.
Keywords: 650; COVID-19; eSports; Gaming; Gold; SVI; VIX